Electrocatalysis in protic and aprotic ionic liquids for energy applications - Smith, Daniel E. (2020)
This thesis documents a study of electrocatalytic reactions pertinent to electrochemical energy conversion using protic ionic liquids (PILs) and aprotic ionic liquids (AILs) as electrolytes. The effect of proton-donating and proton-accepting species on electrocatalytic reactions in ionic liquids are investigated, and the implications for the use of PILs as intermediate-temperature fuel-cell electrolytes are considered. A fundamental understanding of proton-shuttling mechanisms in PIL-based fuel cells is presented.